Gene Expression and Structural Differences Underpinning Black and White Colouration in Spiders - Fabian C. Salgado‐Roa; Devi Stuart‐Fox; Laura Ospina‐Rozo; Iliana Medina (Molecular Ecology, 2026)
The presence of multiple color variants within a single population, known as color polymorphism, is a striking example of intraspecific phenotypic variation and a model for studying evolutionary processes. These processes depend on the underlying mechanisms such as the genes and pigments involved; but we currently lack such information for non‐model groups such as arachnids. We examined the genes associated with color polymorphism in the Australian Christmas spider, Austracantha minax , a widespread species with two female‐restricted color morphs: one that is completely black and the other presenting a black‐and‐white pattern on its dorsum. We sequenced the mRNA of individuals of both morphs at different developmental stages and assessed differences in gene expression between color morphs based on a de novo transcriptome assembly for the species, and integrated this with high resolution electron microscopy observations. We found that gene expression patterns are primarily influenced by the stage of development, and within each stage we found differentially expressed genes between the black and black‐and‐white morphs, especially in the adult stage. Contrary to expectations, these genes were not associated with melanin or guanine crystal deposition (detected in the microscopy), but were associated with chitin and cuticle metabolic processes. By exploring arachnid coloration at the transcriptomic level, our work reveals for the first time genetic mechanisms underpinning the evolution of color polymorphism in spiders.

Body size rather than reflectivity explains thermal constraints on colour variation in an aposematic jewel bug - Kei-Lin M. Ooi; Iliana Medina; Fabian C. Salgado-Roa; Devi Stuart-Fox (Evolutionary Ecology, 2025)
Theory posits that warning signals should converge phenotypically to reinforce predator memory, yet many aposematic species show substantial variation in warning signals within and between populations. This could be explained by alternative selective pressures on phenotype beyond predation such as thermoregulation, but empirical tests are scarce and do not consider the full spectrum of sunlight. To examine whether trade-offs with thermoregulation could explain variation in warning colouration, we examined thermal properties of colour variants of the aposematic cotton harlequin bug ( Tectocoris diophthalmus ). This species shows striking variation in warning signals: it is sexually dichromatic, varies within sexes, and shows clinal variation in colour frequencies, with iridescent blue-green colouration prevalent in cooler climates and non-iridescent red–orange colouration prevalent in warmer climates. We quantified reflectivity between colour variants over the full solar spectrum and investigated the contribution of ultraviolet and visible (UV–visible, 300–700 nm) and near infrared (NIR, 700–1700 nm) light on heating. Differences in reflectivity of iridescent and non-iridescent colour patches were greater in NIR than UV–visible wavelengths but did not result in significant differences in heating. However, we found a tight link between body size and reflectivity, with smaller males having lower reflectivity and heating faster. Due to the strong correlation between body size and colouration, thermal constraints related to body size may help to explain the observed clinal variation in colour frequencies.

The Andes as a semi‐permeable geographical barrier: Genetic connectivity between structured populations in a widespread spider - Fabian C. Salgado‐Roa; Carolina Pardo‐Diaz; Nicol Rueda‐M; Diego F. Cisneros‐Heredia; Eloisa Lasso; Camilo Salazar (Molecular Ecology, 2024)
Geographical barriers like mountain ranges impede genetic exchange among populations, promoting diversification. The effectiveness of these barriers in limiting gene flow varies between lineages due to each species' dispersal modes and capacities. Our understanding of how the Andes orogeny contributes to species diversification comes from well‐studied vertebrates and a few arthropods and plants, neglecting organisms unable to fly or walk long distances. Some arachnids, such as Gasteracantha cancriformis , have been hypothesized to disperse long distances via ballooning (i.e. using their silk to interact with the wind). Yet, we do not know how the environment and geography shape its genetic diversity. Therefore, we tested whether the Andes contributed to the diversification of G. cancriformis acting as an absolute or semi‐permeable barrier to genetic connectivity between populations of this spider at opposite sides of the mountain range. We sampled thousands of loci across the distribution of the species and implemented population genetics, phylogenetic, and landscape genetic analyses. We identified two genetically distinct groups structured by the Central Andes, and a third less structured group in the Northern Andes that shares ancestry with the previous two. This structure is largely explained by the altitude along the Andes, which decreases in some regions, possibly facilitating cross‐Andean dispersal and gene flow. Our findings support that altitude in the Andes plays a major role in structuring populations in South America, but the strength of this barrier can be overcome by organisms with long‐distance dispersal modes together with altitudinal depressions.

Which side are you on? Spider web positioning affects prey capture more than body colour - Fabian C. Salgado-Roa; Devi Stuart-Fox; Edwin Castañeda; Maira S. Tique Obando; Iliana Medina (Evolutionary Ecology, 2023)
Colour has been hypothesized to play a crucial role in prey capture for sit-and-wait predators that rely on visual cues to deceive their prey. Prey capture success has been directly linked to colouration in spiders; however, evidence so far focuses mostly on dorsal colouration, excluding ventral patterns that are visible to prey and may be relevant for prey attraction. Here, we explored whether the dorsal and ventral colouration of a colour polymorphic spider is associated with light environment and prey capture success. We quantified the number of prey captured across three dorsal (black, white, and yellow) and two ventral (black and a mosaic yellow/orange pattern) morphs of Gasteracantha cancriformis , considering light intensity on dorsal and ventral sides. We found that spiders capture more prey in low light environments, and that individuals often expose their dorsal colouration towards low light levels. We did not find significant differences in prey capture rate between morphs dorsally or ventrally. These results indicate that how and where spiders position their web can be more important for prey capture than colouration. Alternative hypotheses such as aposematism, camouflage and thermoregulation deserve more attention in future studies that aim to understand the role of colouration in spiders and the factors causing spider colour polymorphisms.